Integrating dermatology services into a social pediatrics network: 8 years of experience in the RICHER (Responsive, Interdisciplinary/Intersectoral, Child/Community, Health, Education and Research) program. (16th August 2021) - Rehmus, Wingfield; Zarbafian, Misha; Alobaida, Saud; Bland, Clea; Hanson, Denise; McIntosh, Gwyn; Pikksalu, Kristina; Loock, Christine
Abstract: Social pediatric initiatives aim to improve health outcomes for vulnerable children by working in the community to empower families, to enhance protective factors that mitigate adverse childhood experiences (ACEs), and to deliver place‐based health care. In 2012, pediatric dermatology was added as a component of the Responsive, Interdisciplinary Intersectoral Child and Community Health Education and Research (RICHER) social pediatric program in Vancouver, BC. We share our experience with inclusion of pediatric dermatology in a well‐established social pediatric program as well as lessons we have learned in the first 8 years of our partnership. Partnership, bridging trust, knowledge sharing, empowerment, consistency, and flexibility were found to be central elements in the success of this endeavor.